Study of Immunogenicity and Protective Efficacy of Live MDCK-derived Pandemic Influenza Vaccine - Elena A Nechaeva; Ryzhikov AB; Pyankova OG; Radaeva IF; Pyankov OV; Danilchenko NV; Agafonov AP; Kiseleva LV; Larionova NV; Rudenko LG (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2019)
Background: The threat of pandemic A/H1N1 influenza is still a matter of considerable public concern. Influenza outbreak in 2009 underlined the importance of rapid production of a sufficient vaccine reserve for pandemic and interpandemic periods. One promising way to allay this concern is development of cell culture-derived live attenuated influenza vaccines (LAIV), because this technology makes it possible to produce a considerable amount of vaccine over a short period of time. Objectives: The goal of this work was to study the immunogenic and protective properties of the Vector-Flu vaccine in animal models. Methods: We have developed Vector-Flu, a live attenuated vaccine against pandemic influenza, based on the cold-adapted reassortant vaccine strain for LAIV, A/17/California/2009/38(H1N1), and produced in certified MDCK cells. The immunogenicity and protective efficacy of Vector-Flu vaccine were studied in ferrets and mice. Results: A double immunization with the live MDCK-derived Vector-Flu influenza vaccine induced a high level of neutralizing antibodies in ferret serum both to the pandemic A/Chita/3/2009(H1N1) influenza virus strain, isolated in Russia, and to the pandemic A/California/7/2009(H1N1) strain. Intranasal immunization of mice induced levels of serum antibodies sufficient to protect them when aerosol-challenged with 100 infectious doses of A/Chita/3/2009(H1N1) strain.  Conclusion: Theoretical estimates of protective antibody levels necessary for protecting humans from the disease caused by pandemic A/H1N1(2009) influenza virus, and the experimental data from animal models (ferrets and mice), suggest that the Vector-Flu vaccine is able to protect humans after a single immunization.